SCIENTIFIC TERMS IN INDONESIAN MIDWIFERY SCIENCE - Maryam Sorohiti (SEAJOM: The Southeast Asia Journal of Midwifery, 2020)
The use of the term midwifery in Indonesian, of course, comes from many foreign language terms, especially English. This can be a separate study that the terms which are made their equivalent in Indonesian must reflect the scientific terms and truth in terms of meaning and grammar. Therefore, this literature research tries to explore some of the terms used in Indonesian by referring to them in Indonesian grammar and meaning in English. In the results of this study, there were three terms that could be studied in terms of language in order to improve understanding of the midwifery term. The three terms were pijat oksitosin (massage aimed at stimulating the release of the hormone oxytocin), ASI eksklusif, and bendungan ASI. The results of this study are expected to provide input for midwifery researchers and academics in Indonesia to further improve the quality of terms of midwifery that may be found in the future.